Isolation, characterization, and biomedical potential of phycoerythrin phycobiliprotein from Kappaphycus alvarezii (Doty) L. M. Liao: antimicrobial, antioxidant, and anticancer activities - Harinathan Balasundaram; Parthasarathy Seethapathy; Subbiah Sankaralingam; Shunmugiah Mahendran; Murugan Mareeswaran; Jeyaraj Pandiarajan; Pandiaraj Maheswari; Sakthivel Venkatesh; Malaisamy Arunkumar; Girish R. Pathade; Deepu Pandita; Anu Pandita; et al. (Scientific Reports)
Abstract Kappaphycus alvarezii (Doty) L. M. Liao, a red seaweed widely cultivated for carrageenan polysaccharide, is also a potential source of the valuable pigment phycoerythrin (PE). Therefore, this study aims to extract phycoerythrin from K. alvarezii, evaluate its antimicrobial, antioxidant, and anticancer activities, and identify its biomedical potential for future therapeutic applications. The protein content of phycoerythrin pigment extracted from K. alvarezii was found to be 69.84% and showed excellent antimicrobial activity against Klebsiella oxytoca and Proteus mirabilis, with a minimum inhibition zone of 11 mm. It showed significant in vitro antioxidant activity, as analyzed using total antioxidant, hydrogen peroxide scavenging, reducing power, DPPH, and ABTS assays. Further, the pigment exhibited potent cytotoxicity against a human lung cancer cell line, with an IC50 value of 131.7 µg mL−1. Furthermore, increasing concentration of phycoerythrin pigment decreased the cell proliferation and induced apoptosis, as confirmed by Annexin V/PI staining. Comprehensive characterization using FT-IR, HPLC, and GC-MS analysis revealed the nature of pigment and functional groups, highlighting its potential for biomedical applications. The molecular docking of K. alvarezii-derived compounds revealed significant binding affinities with 13 antibacterial target proteins. These results highlight the potential of K. alvarezii bioactive compounds as promising antibacterial agents. The phycoerythrin extract from K. alvarezii demonstrated potent antimicrobial, antioxidant, and anticancer properties, with significant cytotoxicity against lung cancer cells and confirmed apoptosis induction. Structural analysis revealed its bioactive composition, emphasizing its potential as a natural therapeutic agent. These findings support its potential application in the biomedical and pharmaceutical industries.